A practical guide to architectural drawing - Ren, Guang Yu; Denison, Edward; Royal Institute of British Architects (London : RIBA Publishing, 2024)
A visually stunning celebration of architectural drawing, aimed at students, sourced exclusively from the RIBA Collection. Arranged into three parts, the book begins with a historical summary of the drawings in the RIBA's Collection.
Keywords: Architectural drawing; ARCHITECTURE / Design & Drafting